Cross-cultural adaptation and validation of the Italian version of the Hip disability and Osteoarthritis Outcome Score (HOOS) - Marina Torre; Ilaria Luzi; Fiorino Mirabella; Martina Del Manso; Gustavo Zanoli; Gabriele Tucci; Emilio Romanini (Health and Quality of Life Outcomes, 2018)
Abstract Objective To create a translated version of the HOOS to fit the Italian population and to test its psychometric properties and validity in hip osteoarthritis (OA) patients undergoing total hip arthroplasty (THA). Design The HOOS Italian version was developed according to published international guidelines that include preparation, forward translation and reconciliation, backward translation, review and harmonization, and proof reading. The Italian HOOS was administered to 145 patients (mean age 65.7 ± 11.6 years, 34–89, 58.6% women) undergoing THA. The following psychometric properties were evaluated: internal consistency (Cronbach’s alpha); test-retest reliability (Pearson’s r and intra-class correlation coefficient, ICC); convergent validity (Spearman’s rho between HOOS and SF-36); responsiveness (comparison of pre/post-THA scores, Wilcoxon signed rank test). Interpretability (floor and ceiling effects, skewness and kurtosis indexes) and acceptability (time to compiling, missing answers, and autonomy in compilation) were also evaluated. Results Translation and transcultural adaptation were conducted in accordance with the international recommendation. The translation was deemed understandable and appropriate as to the transcultural adaptation. None of the patients reported to have met any difficulties in reading and understanding the HOOS items. Internal consistency and test-retest reliability were good for each HOOS subscale (Cronbach’s alpha ≥0.7, Pearson’s r and ICC > 0.80). Convergent validity showed the highest correlations (Spearman’s rho > 0.5) between HOOS and SF-36 subscales relating to similar dimensions. As to responsiveness, all HOOS subscales scores improved significantly after THA (p < 0.01). Interpretability was acceptable despite ceiling effect in post-THA assessment. Acceptability was good: HOOS resulted easy and quick to fill out (12 min on average). Conclusions The HOOS was successfully cross-culturally adapted into Italian. The Italian HOOS showed good psychometric properties therefore it can be useful to assess outcomes in OA patients after THA. This study provided a basis for its use within the Italian Arthroplasty Registry and for future clinical trials.